Life dreams, appreciative inquiry and empowerment: A study of creative and narrative approaches among university students - Kouroukouni, Anna (Homo Virtualis, 2025)
This study explores the relationship between university students and their life dreams through a qualitative, creative, and narrative research framework. Based on Appreciative Inquiry and a multimodal approach, the research combines semi-structured individual interviews with techniques such as drawing and photo-production. These methods allowed participants to express their dreams in multidimensional ways and reflect on their personal growth, identity, and aspirations. The findings highlight the interplay between self-awareness, self-esteem, and the challenges faced by young individuals in academic environments. Empowerment emerges through supportive networks and affirming experiences, while life dreams are framed as acts of resistance to societal and familial pressures. A recurring theme is the refusal to compromise, which participants embrace as a life philosophy. Through the combination of verbal and non-verbal data, this study aims to bring to light the richness of university-student experiences, emphasizing the role of creative expression in constructing meaningful life narratives. It invites dialogue about how psychology and the social sciences can support youth empowerment by cultivating spaces of appreciation, possibility, and authenticity.